Phase diagram for the co-adsorption of O and OH on Pt(100) and Pt(111) as determined by DFT - Cilliers, Pierre Louis (Department of Chemical Engineering, 2018)
The Langmuir adsorption isotherm is often used to model molecular adsorption on catalyst surfaces. The model assumes that adsorption occurs on a homogenous energy surface at specific localized sites with no lateral interactions between adsorbents. This simplification causes some concerns when considering adsorption at higher coverages as species have been observed to have a maximum coverage less than one monolayer (ML), such as O and OH on platinum (Pt) surfaces for use in direct methane to methanol synthesis. It has been suggested that the maximum coverages are due to repulsive lateral interactions which limit coverages on Pt to 0.50 ML and 0.75 ML for O and OH respectively, weakening the Langmuir assumption. For reactions sensitive to coverage it is useful to have a model representation of these interactions and the obtainable coverages. This would require determining the effect these interactions have on obtainable coverages and whether possible hydrogen bonding could allow for co-adsorption to fully saturate Pt catalysts. Thus, this study focuses on the coverage of Pt surfaces with O, OH and co-adsorbed O/OH adsorbents as a function of temperature and partial pressure with particular interest given to full coverage conditions. To determine the obtainable coverages on the dominant Pt surfaces, namely Pt(100) and Pt(111), a Density Functional Theory (DFT) study was done using a GGA-PBE and GGA-optB88 model utilising VASP. The coverages were modelled on a p(2x2) Pt cell which could model 0.25, 0.50, 0.75 and 1.00 ML. The relative Gibbs free energies were then calculated for all adsorbent combinations on the surface with oxygen and water as the gas phase reference. The change in Gibbs free energy upon adsorption was calculated across a chemical potential range of -0.22 eV, corresponding to the critical point for O2 (-118.6 °C, 50.06 bar), up to -3.5 eV. These chemical potentials were then related to specific temperatures and partial pressures. It was found that only full coverage with OH was achievable on Pt(111). In contrast, Pt(100) yielded several full coverage combinations. The generation of these phase diagrams showed a trend of increasing lateral interactions that prevent full coverage with a single O adsorbent species. As shown, by co-adsorbing OH it could be possible to achieve higher coverages through attractive lateral interactions. This weakens the lateral interaction assumption used in the Langmuir model and indicates the possibility of low temperature direct methane to methanol synthesis, around 80 °C, due to the formation of a fully saturated Pt surface.